The Semantics of “New” Batik Clothes: Identifying Users’ Perception on the Colors and Patterns of Newly Developed West Javanese Batik Clothes - Achmad Syarief; Yan Yan Sunarya (ITB Journal Publisher, LPPM ITB, 2007)
Batik is a traditional textile art of Indonesia, in which through its appearance we may excerpt the customs, traditional values, way of life, spiritual meanings, and cultural characteristics of Indonesian people. Previous researches on batik have-for the most part-uncovered and elaborated batik as a solely artifact of art, distancing its relation with those who use it. As results, most of batik research tends to frame batik as an object of preservation and do not elaborate more on the context of batik as an object of perception (of users) or batik as an object of consumption. To address this issue, the paper explores perceptual identification of batik users using semantic differential method, evaluating actual users’ perception on the element of colors applied on clothes of West Javanese batik as object of study. The obtained data will be cross-referenced to identify gender and subject-experience variables. The implication of the findings for the creative process and marketability of batik will be discussed, in hoping to gain applicable knowledge for the preservation as well as new development of West Javanese batik design.